SEARCH FOR ORIGIN: NAVIGATING TO FIND THE REAL ROOTS IN LISA KO’S THE LEAVERS AND NICOLE CHUNG’S ALL YOU CAN EVER KNOW: A MEMOIR OF ADOPTIO - Silpa S, Ashika S Kumar, Aiswarya Vasanth (Obstetrics and Gynaecology Forum, 2024)
Abstract Transracial adoption involves placing children from a particular race and ethnic group with parents of different race and ethnicity than their own. This difference often puts the transracial adoptees in a state where they question their own identity. They always live in a dilemma pondering over the thought that they neither belong to their native culture nor to their adoptive culture. Both Lisa Ko’s The Leavers and Nicole Chung’s All You Can Ever Know: A memoir of adoption portrays the hardships and internal conflicts faced by transracial adoptees in their struggles to assimilate into the new environment. Thus, the analysis of the books depicts issues of identity crisis faced by transracial adoptees, their journey of self-discovery and questioning of their identity. The prejudiced views of society in turn put them in situations where they questioned their self-worth. But ultimately with the love and support of people around them they could regain confidence in their sense of self. It proved the crucial role played by people, in the identity formation of a transracial adoptee. Thus, the paper proves that social support from family and friends could reduce the negative impact of identity crisis in a transracial adoptee. The paper also seeks to prove that transracial adoptees face more identity crisis than same race adoptees. The paper also looks for the causes and consequences of a transracial adoptee's identity crisis. Thus, the paper could promote awareness about the problems of transracial adoptees and thereby create a more inclusive society.